The Impact of Religious Institutions on Economic Growth in Indonesia : Evidence from Selected Province - Listiono Listiono (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2020)
In recent years, the study of the influence of religion on the economy is rising. However, in Indonesian context there is limited number of literature that specifically explores the relationship between religion and economic. To fill this gap, this article aims to investigate the effect of religion –with religious institutions as proxies- on economic growth using panel data from 2010 to 2017 of selected provinces. This model based on the Cobb-Douglas model and estimated using fixed-effects. The result shows that economic growth positive significantly affected by Protestant and Hindu variables. On other side, there in no strong evidence that Islam and Catholic have siginificant impact on economic growth. This paper does not claim that one religion is better than others in terms of economic activity, as measured by economic growth, but rather on how the role of religious institutions on social networks encourage economic growth. An important point of this paper is that in Indonesian context, religion has significant influences on the economic growth as in many other countries. Keywords: Religion, economic growth, Indonesia, fixed-effects